Heart Rate Responses in Show‐Jumpers Over A Three‐Day Training Session. (June 2014) - Harris, P; Roberts, C; Armstrong, S; Murray, R; Handel, I
Abstract : Introduction: The objective of this study was to provide more information regarding the relationship between heart rate (HR) and performance in show‐jumpers. Methods: Ten mixed breed horses (9.1 ± 1.9 yrs) were assessed at a British Equestrian Federation (BEF) World Class Performance three‐day training session. Riders received coaching during warm‐up (WU) and after jumping a 15 fence (1.35–1.45 m) course once on day‐1, twice on days 2 & 3; on day‐3 the second round was an 8‐fence jump‐off. Clinical assessments were performed, and plasma lactate concentrations determined, pre‐ and post‐exercise. Take‐off distance (TDF) was determined using high‐speed motion capture. The coach graded horse jumping technique (validated methodology). HR was recorded telemetrically from WU until 10 mins post‐exercise. Variables were compared using regression procedures/Spearman correlation and paired Students t‐test (P<0.05). Results: HR was not significantly different between days or consecutive jumping rounds. Mean HR was lower in WU than during the course (127 ± 11 vs 136 ± 16: P = 0.027), likely related to increased speed during the course, although HRpeak tended to be higher during WU day‐ 1 possibly reflecting excitement. Mean HR increased for each quarter during the course. Higher mean course and third‐quarter HR were associated with higher blood lactate concentrations (P = 0.047), greater gluteal and longissimus dorsi muscle spasm on palpation (P<0.01), more faults (P = 0.044) and lower technique scores (P = 0.019). TDF was negatively correlated with mean course and third‐quarter HR, indicating that closer take‐off may be harder work (P<0.01). Conclusions: HR increases throughout a jumping course. Higher HRs may be associated with jumping inefficiency and muscle spasm, with potential performance implications for multi‐day competitions. Ethical Animal Research: Explicit owner informed consent for participation in this study is not stated.Sources of funding: The World Class Development Programme is funded by the Department for Culture, Media and Sport, through Exchequer and National Lottery funds, via UK Sport.Competing interests: none.